2004
DOI: 10.1111/j.1467-8543.2004.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Collective Bargaining and Within‐firm Wage Dispersion in Spain

Abstract: This paper analyses the effect of collective bargaining on within-firm wage dispersion for the case of Spain. What is relevant in the Spanish case is to compare the effect of the two basic levels of bargaining (firm and sector) on wage dispersion. By using the Oaxaca-Blinder decomposition, this paper concludes that collective agreements at firm level have a negative effect on wage dispersion. At the same time, firms that have signed these types of agreements show greater wage dispersion than those covered by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Canal Domínguez and Rodriguez Gutiérrez (2004) analyse the effect of firm bargaining on within-establishment wage dispersion in Spain. They find that signing a collective agreement at the firm level tends to reduce wage dispersion; however, other characteristics of the firms covered by SEB, such as their size and average workers' education level, more than outweigh this effect, so that on the whole these firms show greater internal wage dispersion.…”
Section: Centralization Of Bargaining and Wage Dispersion: Previous Ementioning
confidence: 99%
“…Canal Domínguez and Rodriguez Gutiérrez (2004) analyse the effect of firm bargaining on within-establishment wage dispersion in Spain. They find that signing a collective agreement at the firm level tends to reduce wage dispersion; however, other characteristics of the firms covered by SEB, such as their size and average workers' education level, more than outweigh this effect, so that on the whole these firms show greater internal wage dispersion.…”
Section: Centralization Of Bargaining and Wage Dispersion: Previous Ementioning
confidence: 99%
“…Overall, the final outcome of company bargaining on the withinfirm wage dispersion seems ambiguous: Dell'Aringa and Lucifora (1994b) found no difference in within-firm wage dispersion between firms covered only by a multi-employer agreement and those covered additionally by a company agreement. Conversely, Dominguez and Rodriguez-Gutiérez (2004) found that company bargaining reduces the within-firm wage dispersion in Spain. They attribute this result to the action of unions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, wage bargaining occurs at different levels: national, sectoral, regional and/or local. Several studies have shown that the level of collective wage bargaining has an impact on the dispersion of wages within and between establishments (Dell'Aringa and Lucifora, 1994; Dominguez and Gutierrez, 2004;Plasman et al, 2005;Card and de la Rica, 2006;Dell'Aringa and Pagani, 2007). However, there is no consensus about the sign of this effect.…”
Section: Theorymentioning
confidence: 86%